ANALYSIS OF COMPETENCE AND INTEGRITY ON TEACHER PERFORMANCE WITH JOB SATISFACTION AS AN INTERVENING VARIABLE AT SMA NEGERI 1ELEPHANT TIMANG, BENER MERIAH REGENCY - M. Thaib; Sri Rahayu; Kiki Farida Ferine (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study aims to analyze the influence of competence and integrity on teacher performance with job satisfaction as an intervening variable at SMA Negeri 1 Timang Gajah, Bener Meriah Regency. The background of this study is based on the important role of teachers in improving the quality of education, where teacher performance is influenced by internal factors such as competence and integrity, as well as external factors such as job satisfaction. This study used a quantitative approach with a population of 77 teachers, all of whom were sampled using a saturated sampling technique. Data collection was carried out by distributing questionnaires and processed using the Partial Least Square (PLS) method. The results showed that competence had a positive and significant effect on teacher performance and job satisfaction. Integrity had a positive and significant effect on job satisfaction, but a positive but not significant direct effect on teacher performance. Job satisfaction was proven to have a positive and significant effect on teacher performance and was an intervening variable in the relationship between competence and integrity on teacher performance. These findings indicate that efforts to improve teacher performance need to be focused on strengthening competence, upholding integrity, and creating a work environment that supports job satisfaction. The results of the study are expected to be a reference for schools in formulating policies for sustainable teacher professional development.